2018
DOI: 10.25100/cm.v49i2.2522
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneidad clínica y mutacional en pacientes colombianos con Pelizaeus Merzbacher

Abstract: Case Presentation: Pelizaeus Merzbacher Disease (PMD) is an X-linked developmental defect of myelination that causes childhood chronic spastic encephalopathy. Its genetic etiology can be either a duplication (or other gene dosage alterations) or a punctual mutation at the PLP1 locus. Clinically, it presents with developmental delay, nystagmus and, spasticity, supported by neuroimaging in which the defect of myelination is evident. We present a series of seven Colombian patients diagnosed with this leucodystrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Although we did not collect data for the date of diagnosis, these results highlight the challenges many patients and families face with receiving a timely diagnosis of Pelizaeus-Merzbacher disease, which is an important consideration for the development of disease modifying therapeutics where early intervention is key. Consistent with the literature, 3,17 we found that across all phenotypes the most frequently reported symptoms are difficulty with gross and fine motor skills, speech, and communication. For the most common phenotypes of classic and connatal Pelizaeus-Merzbacher disease, difficulty with communication; difficulty eating and/or swallowing; difficulty with crawling, standing, or walking; difficulty with manual dexterity; nystagmus; difficulty learning; and spasticity are all reported as common symptoms in both groups (>50%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although we did not collect data for the date of diagnosis, these results highlight the challenges many patients and families face with receiving a timely diagnosis of Pelizaeus-Merzbacher disease, which is an important consideration for the development of disease modifying therapeutics where early intervention is key. Consistent with the literature, 3,17 we found that across all phenotypes the most frequently reported symptoms are difficulty with gross and fine motor skills, speech, and communication. For the most common phenotypes of classic and connatal Pelizaeus-Merzbacher disease, difficulty with communication; difficulty eating and/or swallowing; difficulty with crawling, standing, or walking; difficulty with manual dexterity; nystagmus; difficulty learning; and spasticity are all reported as common symptoms in both groups (>50%).…”
Section: Discussionsupporting
confidence: 91%
“…7-11 Studies that investigate the natural disease course and clinical phenotypes of Pelizaeus-Merzbacher disease have been small and often limited to individual case series. 12-17 Prior to any potential disease-modifying therapy entering the clinic, it is important to assess the impact of the disease from the participant and caregiver perspectives to enable appropriate evaluation of potential benefit in this population. 18…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All our patients exhibited onset within the first year of life, with nystagmus predominating as the first symptom noticed, consistent with previous reports. 7,8,10,11 In addition, most had nystagmus at some point in their lives and all had hypotonia, key characteristics of the classic PMD phenotype. In our cohort, all of our subjects exhibited delays in both motor and language development; however, many individuals were able to meet several developmental milestones.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 , 10 , 11 In addition, most had nystagmus at some point in their lives and all had hypotonia, key characteristics of the classic PMD phenotype. Velasco Parra et al 12 reported on seven Columbian patients with Pelizaeus–Merzbacher disease ranging in age from 6 to 16 and with various PLP1 pathogenic variants. Unlike in our cohort.…”
Section: Discussionmentioning
confidence: 99%